PENGARUH PENGHINDARAN PAJAK DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK - , (Jurnal Akuntansi Pajak dan Manajemen (TAJAM), 2023)
Tax avoidance is a way to avoid legal tax payments made by taxpayers by reducing the amount of tax owed without breaking tax regulations or in other terms looking for regulatory weaknesses. At this stage, the taxation regulations are collected and researched so that actions in tax savings can be selected so that tax evasion behavior can be generated. Although tax avoidance is the right of every taxpayer does not mean there are no sanctions for violators. Imposing sanctions that are burdensome and fair are expected to increase taxpayer compliance in reporting its Annual Notification Letter. These problems become obstacles in tax revenue. The purpose of this study was to analyze the effect of tax avoidance, tax sanctions on taxpayer compliance in the KPP Pratama Purworejo. The population used in this study is corporate taxpayers registered in KPP Pratama Purworejo. This study uses a simple random sampling method by determining samples based on criteria determined in the study. The sample of this study was 100 respondents of corporate taxpayers in KPP Pratama Purworejo. Data collection methods used are primary data using a questionnaire. Data analysis technique used in this study is multiple linear regression analysis techniques. Based on the results of the analysis conducted, it was concluded that the tax avoidance variable had a positive and significant effect on corporate taxpayer compliance with a coefficient value of 0,207, while the tax sanction variable had a positive and significant effect on corporate taxpayer compliance with a coefficient value of 0,678. Simultaneously the variables of tax avoidance and tax sanctions have a significant effect on taxpayer compliance with a calculated f count of 89,923. Keywords: tax avoidance, tax sanctions and taxpayer compliance.